Writing using sources for academic purposes : theory, research and practice - Wette, Rosemary (Routledge, 2021)
Writing Using Sources for Academic Purposes: Theory, Research and Practice provides research-based information about key components of source-based writing, and the challenges it presents for novices. Proficiency in source-based writing is an essential and challenging goal for all inexperienced academic writers, from both L1 and L2 backgrounds. This comprehensive book presents an innovative, integrated approach for graduate students, teaching faculty, and practice-oriented researchers in ESP/EAP around the world. Each chapter includes suggestions and sample tasks for self-study or classroom use. Incorporating reviews of research and scholarly knowledge as well as information about likely challenges for novices, the book examines: (1) Changing views on the origins of novices' difficulties (2) Pre-writing tasks that writers need to work through, from locating and evaluating sources to proficient reading-to-write and summarizing strategies (3) Citing types and purposes (4) The more sophisticated abilities of conveying an appropriate stance and engaging with readers (5) Disciplinary citing practices This book will be of interest to undergraduate and postgraduate writers from a variety of backgrounds, as well as their teachers and supervisors. It will be relevant to the growing number of researchers from non-English speaking backgrounds who are obliged to publish their work in English language international journals, and scholars who may be interested in carrying out research related to source-based writing.- Resumé vydavatel
Keywords: angličtina; rétorika; odborné texty; bibliografické citace; psané texty; studium a výuka; vysokoškolské studium; English language; rhetoric; professional texts; standard citation forms; written texts; study and teaching; college study; akademické psaní; elektronické knihy; příručky; electronic books; handbooks and manuals